The role of international law in controlling disease outbreaks. (12th May 2021) - Banerjee, Rajat; Kumar, Abhinav
Disease outbreaks in the form of epidemics and pandemics are known to destabilise the existing global public health infrastructure and to put nation-states in an alarming set of circumstances, thereby posing quite a few questions before us, including: can there be a solution to such problem in international law? In light of this question, the present essay tries to discern the role of international law in handling disease outbreaks. It wants to know whether there are sufficient international legal safeguards to address disease outbreaks and whether liability can be fastened on nation-states (including their people), international organisations, etc., if they are found to be directly and substantially responsible for such outbreaks. It dissects theoretical frameworks, analyses and interprets the existing literature to conclude that a 'one-size-fits-all' international legal approach is required to control disease outbreaks. It eventually recommends the need to have a Pandemic Convention.